Functional and Histological Evaluation following Canine Vocal Fold Reconstruction Using Combined Thyroid Ala Perichondrium Flaps. (2nd September 2014) - Glab, Rachel C.; Gunderson, McLean; Hoffman, Matthew R.; Maytag, Allison L.; Yang, David; Jiang, Jack J.; Dailey, Seth H.
Abstract : Objectives: (1) Perform vocal fold reconstruction using composite thyroid ala perichondrium (CTAP) flaps in beagles following unilateral vocal fold stripping; (2) Evaluate aerodynamic, acoustic, vibratory, and histologic changes in canines undergoing CTAP‐based vocal fold reconstruction compared to a control group undergoing injury alone. Methods: Unilateral vocal fold stripping was performed on ten beagles. Dogs healed for 1 month and were divided into 2 groups. Dogs in the control group (n = 5) were sacrificed. Dogs in the experimental group (n = 5) underwent ipsilateral vocal fold augmentation with a CTAP flap and recovered for 1 month prior to euthanasia. After euthanasia, larynges were harvested for excised larynx evaluation of vocal fold vibration using aerodynamic, acoustic, and mucosal wave measurements. Histological analysis was then performed on anterior, middle, and posterior sections of the vocal fold. Changes in the injured fold were compared between the control and experimental groups. Comparisons with the contralateral normal fold were made within the control and experimental groups. Results: Phonation threshold pressure was significantly lower in the treatment group ( P =. 005). Percentage jitter ( P =. 010) and shimmer ( P =. 007) were also lower in the treatment group. Open quotient was significantly higher in the control group ( P =. 007). Histological staining results were inconsistent, and gross analysis revealed evidence of surgical implantation without restoration of normal vocal fold architecture. Conclusions: CTAP‐based vocal fold augmentation restored glottic closure and vibratory periodicity following vocal fold scarring. Additional investigation on biologic response is warranted. CTAP flaps offer an autologous, vascularized implant that can improve both vocal fold structure and function.